(untitled) (Revista de Estudos da Linguagem, 2003)
The aim of this article is to discuss the way the Portuguese Creoleof Guinea-Bissau codifies the semantically opposite actions ofundoing (DE-ACTION) and redoing (RE-ACTION) an act, not onlymorphologically, but also semantically and ecologically, i.e., intheir interralations with the social ecosystem of which they arepart. ln the lexifier language (Portuguese), they are codifiedprefixally, namely, by means of des- ‘un-, de-’ and re- ‘re-’,respectively. Using the methodology of corpus linguistics, I showthat the creole codifies only DE-ACTION morphologically, via theprefix dis-. As to RE-ACTION, lt is expressed only syntactically, bymeans of the equivalent of “again”, exactly as in children’s speech.The findings are compared to what happens in other lexifier creolesand in Portuguese. Some suggestions are given for why creole hasonly the prefix dis-, but not its opposite. Finally, I suggest that thebehavior of dis- in this language calls for an independentmorphological component of the grammar roughly like what canbe seen in lexical phonology and morphology.